PH-Dependent morphology and optical properties of lysine-derived molecular biodynamers. (30th January 2020) - Lee, Sangeun; Kaya, Cansu; Jang, Hongje; Koch, Marcus; Loretz, Brigitta; Buhler, Eric; Lehr, Claus-Michael; Hirsch, Anna Katharina Herta
Abstract : The spherical micelles of the carbazole monomer transformed into nanorods in the course of the polymerization. The polymeric nanorods show pH-dependent changes in fluorescence emission and size. Abstract : Polymerization of carbazole dicarboxaldehydes and lysine derivatives by imine and acylhydrazone formation afforded peptide-derived molecular biodynamers. Characterization of their physicochemical properties revealed an interesting morphology change upon polymerization from monomers forming submicrometer spherical micelles to nanometer-sized rigid-rod-shaped polymeric particles. A combination of light-scattering methods, small-angle neutron scattering, and transmission electron microscopy enabled a detailed investigation of this morphological change. Moreover, we investigated by dynamic and static light scattering how the pH affects the fluorescence and size of the biodynamers. These morphological and pH-dependent changes are expected to open the door to a myriad of applications of molecular biodynamers.